Rumination's effect on suicide ideation through grit and gratitude: A path analysis study. (May 2017) - White, Evan J.; Kraines, Morganne A.; Tucker, Raymond P.; Wingate, LaRicka R.; Wells, Tony T.; Grant, DeMond M.
Abstract: The current study documents the relationship between suicide ideation, grit and gratitude, and rumination subtypes of brooding and reflection. The relationship between rumination and suicide ideation has been well documented and previous research has demonstrated that grit and gratitude are protective factors against suicide. We hypothesized that both subtypes of rumination would have an indirect effect on suicide ideation through levels of grit and gratitude. Results of a conditional indirect effects path analysis indicated that brooding was indirectly related to suicide ideation through gratitude. Brooding interacted with grit such that it only predicted suicide ideation at low levels of grit. Reflection interacted with gratitude to predict levels of grit. Results suggest that brooding may impact suicide risk and resilience through its effect on gratitude, indicating important cognitive-behavioral targets for suicide prevention strategies. These results extend the literature about the relationship between well known risk factors for suicide and protective factors. Highlights: Indirect effect of brooding on suicide ideation through gratitude. No indirect effect of brooding on suicide ideation through grit. Reflection was unrelated to suicide ideation through gratitude and grit.